Emancipation, Democracy and the Modern Critique of Law Reconsidering Habermas - Spång, Mikael (International Political Theory,, 2018)
This book focuses on Jürgen Habermas' theorising on law, rights and democracy in light of the modern critique of law. The latter tradition, which goes back to Hegel and Marx, has addressed the limitations of rights as vocabulary of emancipation and law as language of autonomy. Since Habermas claims that his reconstruction of private and public autonomy has an emancipatory aim, the author has chosen to discuss it in the context of the modern critique of law. More specifically, the study addresses the need to consider the dialectic of law, in which law is both a condition for emancipation and domination, when discussing what law and rights make possible. It will appeal to students and scholars across the fields of political theory, law and legal criticism, as well as sociology and sociology of law.